Implementation of Decency Test and Strategic Position Feasibility in accordance with Law Number 5 of 2014 in Medan City Government, Deli Serdang Regency and Samosir Regency - Robinson Sembiring; Muba Simanihuruk (Jurnal Administrasi Publik (Public Administration Journal), 2020)
This study seeks (1) to explore local government strategies in selecting personnel for strategic positions; (2) studying the role of the RPA (Regional Personnel Agency) in carrying out the Decency and Appropriateness Test of personnel applying for the "Position Auction"; (3) studying the role of the Sekwilda in conducting the fit and proper test; (4) searching for the fit and proper test models according to local characteristics. The agenda for improving Indonesia's public sector becomes a necessity if it is linked to developments and current demands, such as good governance, professionalism, transparency, accountability, ethical and moral enforcement in the delivery of public services (Milakovich and Gordon, 2007 in Nurprojo, 2014). The improvement of the Indonesian bureaucracy through the enactment of the State Civil Apparatus Law is expected to be able to realize a better Indonesian bureaucracy through the performance of professional civil servants based on competence and competition by establishing a merit system in State Civil Apparatus management.  This study uses a qualitative paradigm by relying on researchers as data collectors through in-depth interviews and participatory observation. In-depth interviews were conducted with local elites (Head of the Regional Personnel Agency, Staff of the Regional Personnel Agency, Members of the Regional People's Representative Council, Members of the Selection Committee, Non-Governmental Organizations, the media and intellectuals) who were concerned with local governance. This is done to determine the implementation of the propriety test and due diligence in the context of filling strategic positions in the regions.